2022
DOI: 10.1111/1750-3841.16076
|View full text |Cite
|
Sign up to set email alerts
|

Bentong ginger oleoresin mitigates liver injury and modulates gut microbiota in mouse with nonalcoholic fatty liver disease induced by high‐fat diet

Abstract: The present study aimed to examine the protective effect of Bentong ginger oleoresin (BGO) on the occurrence of nonalcoholic fatty liver disease (NAFLD) and its underlying mechanism. In the present study, 14-week BGO treatment reduced the high-fat diet (HFD)-induced obesity. The serum total cholesterol (TC) was reduced from 4.76 ± 0.30 to 3.542 ± 0.49 mmol/L and fatty liver score decreased to the normal level (1.6 ± 0.55). BGO had antihypercholesterolemia activity, alleviated abnormal lipid metabolism, and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…PPAR α is the main regulator of liver β- oxidation and microsomal ω oxidation, and CPT-1 is its downstream gene [ 37 ]. In the study of nonalcoholic fatty liver, it has been found that inhibiting the expression of PPAR α and its downstream genes in the liver could reduce the β -oxidation of fatty acids and promote the accumulation of fatty acids in the liver [ 38 , 39 ]. The in vivo experiment of this study found that the expression of the PPAR α gene was lower in the NaAsO 2 group than in the control group, which indicated that NaAsO 2 inhibited the β- oxidation of fatty acids in hepatocytes and promoted the accumulation of lipids in the liver [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR α is the main regulator of liver β- oxidation and microsomal ω oxidation, and CPT-1 is its downstream gene [ 37 ]. In the study of nonalcoholic fatty liver, it has been found that inhibiting the expression of PPAR α and its downstream genes in the liver could reduce the β -oxidation of fatty acids and promote the accumulation of fatty acids in the liver [ 38 , 39 ]. The in vivo experiment of this study found that the expression of the PPAR α gene was lower in the NaAsO 2 group than in the control group, which indicated that NaAsO 2 inhibited the β- oxidation of fatty acids in hepatocytes and promoted the accumulation of lipids in the liver [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_NK4A136_group, a distinguishing feature of gut dysbiosis, had higher levels in rats or mice with diseases such as type 2 diabetes, colitis, and NAFLD ( 81–84 ). Thus to decrease the relative abundance of Lachnospiraceae_NK4A136_group might be the key to slowing the development of these diseases ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_NK4A136_group, a distinguishing feature of gut dysbiosis, had higher levels in rats or mice with diseases such as type 2 diabetes, colitis, and NAFLD ( 81–84 ). Thus to decrease the relative abundance of Lachnospiraceae_NK4A136_group might be the key to slowing the development of these diseases ( 81 ). The level of Lachnospiracea_NK4A136_group, which was strongly related to hyperlipidemia indicators, improved high-fat diet-induced glucose and lipid metabolic disorders ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the metabolic modulating function of ginger [ 13 , 14 , 24 , 30 ]. Our previous study showed that ginger oleoresin has the function of regulating blood glucose metabolism in mice, and 6G comprises the biggest proportion of active ingredients in ginger oleoresin [ 22 ]. As far as we know, the present work is the first to offer evidence that supplementation with 6G, an active substance in ginger, helps to improve HFD/STZ-induced prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The mice satisfying the prediabetes criteria were randomized into the DC (prediabetic control) group ( n = 8) receiving HFD and 2 other prediabetic groups receiving HFD plus an additional 10 mg/kg·body weight (BW) 6-gingerol ( w / w , HFD+6G, n = 8). During the dosage choice, our prior work was consulted [ 22 ]. Throughout the experiment, food ingestion was documented twice weekly, while body mass was documented on a weekly basis.…”
Section: Methodsmentioning
confidence: 99%